R.I.A - radioactive isotopes and autoradiography / Haidah Farhanah Hamdan ... [et al.] - Hamdan, Haidah Farhanah; Rosidi, Muhammad Hazim; Mazlan, Siti Nur Izzati; Abu Samah, Siti Nurul Atikah; Yusuf, Nor Azma (Universiti Teknologi MARA, Kedah, 2023)
Teaching aids play a crucial role in enhancing the learning by providing visual and interactive tools to facilitate understanding. In this context, the innovation of R.I.A (Radioactive Isotopes and Autoradiography) as a teaching aid offers a unique and effective approach to teaching complex scientific concepts related to radioactivity and its application. R.I.A incorporates the use of radioactive isotopes and autoradiography techniques to visualize the distribution of radioactivity in biological samples. By introducing this innovative teaching aid, educators can engage students in a hands-on learning experience, enabling them to comprehend the principles of radioisotopes and their role in various fields such as medicine, biology, and agricultural sciences. The use of R.I.A provides several benefits in the teaching process as it contains videos, quizzes, and puzzles to enhance students’ understanding of this topic. R.I.A allows students to explore the applications of radioisotopes in diagnostic imaging, radiation therapy, and scientific research, thereby promoting critical thinking and problem-solving skills. Moreover, R.I.A offers a safe and controlled environment for students to study radioactivity. The incorporation of modern radiation safety protocols ensures that students can interact with radioactive materials responsibly, while also instilling a sense of respect and caution regarding the potential hazards associated with radioisotopes. In conclusion, the innovation of R.I.A as a teaching aid provides a valuable tool for educators to teach complex scientific concepts related to radioactivity. By combining hands-on experimentation with visual representation, R.I.A facilitates a deeper understanding of the principles and applications of radioisotopes, empowering students with the knowledge and skills necessary for future scientific endeavors.